Exploring New Frontiers in Marine Radioisotope Tracing – Adapting to New Opportunities and Challenges - Cresswell, Tom; Metian, Marc; Fisher, Nicholas S.; Charmasson, Sabine; Hansman, Roberta L.; Bam, Wokil; Bock, Christian; Swarzenski, Peter Wolfgang (Frontiers in Marine Science, 2020)
Radioisotopes have been used in earth and environmental sciences for over 150 years and provide unique tools to study environmental processes in great detail from a cellular level through to an oceanic basin scale. These nuclear techniques have been employed to understand coastal and marine ecosystems via laboratory and field studies to understand how aquatic organisms respond to environmental stressors including temperature, pH, nutrients, metals, organic anthropogenic compounds and biological toxins. Global marine issues, such as ocean warming, deoxygenation, plastic pollution, ocean acidification, increased duration and intensity of toxic harmful algal blooms (HABs), and coastal contamination are all impacting marine environments, thereby imposing various environmental and economic risks. Being able to reliably assess the health of coastal and marine ecosystems, and how they may respond to future disturbances, can provide vital information for society in the sustainable management of their marine environments. This paper summarises the historical use of radiotracers in these systems, describes how existing techniques of radioecological tracing can be developed for specific current environmental issues and provides information on emerging issues that would benefit from current and new radiotracer methods. Current challenges with using radioecological tracers and opportunities are highlighted as well as opportunities to maximise the uptake of these methods to greatly increase the ability of environmental managers to conduct evidence-based management of coastal and marine ecosystems.